2011
DOI: 10.1105/tpc.111.085514
|View full text |Cite
|
Sign up to set email alerts
|

RopGEF7Regulates PLETHORA-Dependent Maintenance of the Root Stem Cell Niche inArabidopsis     

Abstract: The root stem cell niche defines the area that specifies and maintains the stem cells and is essential for the maintenance of root growth. Here, we characterize and examine the functional role of a quiescent center (QC)-expressed RAC/ROP GTPase activator, RopGEF7, in Arabidopsis thaliana. We show that RopGEF7 interacts with At RAC1 and overexpression of a C-terminally truncated constitutively active RopGEF7 (RopGEF7DC) activates RAC/ROP GTPases. Knockdown of RopGEF7 by RNA interference causes defects in embryo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
85
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(88 citation statements)
references
References 67 publications
1
85
0
Order By: Relevance
“…There are only two studies that show homeotic transformation of cotyledons into roots: one by the expression of either a dominant-negative version of Rab5 GTPase Ara7 or RNA interference of a Rab5-GEF gene, AtVps9a (Dhonukshe et al, 2008); and one by expressing constitutively active RopGEF7 (Chen et al, 2011). In the former case, auxin response maxima at the tips of developing cotyledons were larger in transgenic plants than those in wild type (Dhonukshe et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…There are only two studies that show homeotic transformation of cotyledons into roots: one by the expression of either a dominant-negative version of Rab5 GTPase Ara7 or RNA interference of a Rab5-GEF gene, AtVps9a (Dhonukshe et al, 2008); and one by expressing constitutively active RopGEF7 (Chen et al, 2011). In the former case, auxin response maxima at the tips of developing cotyledons were larger in transgenic plants than those in wild type (Dhonukshe et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Two reports indicated that ROPGEF1 and ROPGEF7 have specific functions during embryo development. ROPGEF7 RNA interference (RNAi) plants displayed compromised stem cell maintenance in embryo and roots (Chen et al, 2011). The ropgef1 mutants are characterized by defective embryo development and embryo auxin distribution and a mild gravitropic response phenotype , suggesting that the ROPGEF1 function in embryos is unique.…”
Section: Ropgefsmentioning
confidence: 99%
“…It was hypothesized that the regulation of secondary cell wall patterning might rely on receptor-like kinases acting upstream of the RopGEF-ROP module [30]. The Arabidopsis RopGEF7 interacting with ROP3 is required for polar auxin transport and meristem maintenance in the root [25]. Considering their overlapping expression patterns and direct interaction in a yeast two-hybrid assay, the FERONIA receptor kinase has been proposed as a potential upstream regulator of RopGEF7 [18,24].…”
Section: Further Ropgef-rop Signalling Modules Potentially Linked To mentioning
confidence: 99%
“…The identification of rop or ropgef mutants with clavata1 mutant-like phenotypes (enlarged shoot and flower meristems, additional lateral organs, and/or disrupted organ placements) could provide genetic evidence for the role of the potential CLAVATA1-RopGEF-ROP complex in shoot meristem maintenance. Null mutations of these genes might cause embryo lethality, similarly to the ropgef7 mutation that affects the root meristem development negatively and results in non-viable embryos [25]. The silencing of rop and/or ropgef genes would be an alternative approach that could result in viable transgenic plants with decreased RNA levels, allowing the investigation of postembryonic phenotypes [25].…”
Section: The Clavata1 Receptor Kinase Complexmentioning
confidence: 99%
See 1 more Smart Citation